Hungary : Recent Economic Developments and Background Issues. (IMF Staff Country Reports; Country Report ;, 1995)
This paper reviews economic developments in Hungary during 1993-94. The downward trend in measured aggregate output that had begun in 1990 reached its trough during 1993, and Hungary recorded its first positive GDP growth in five years in 1994. At the same time, progress with respect to inflation remained slow and the annual increase in consumer prices, after some decline early in the year, stood at about 21 percent at end-1994, little changed from 1993. Overall, macroeconomic developments in Hungary during 1993-94 were overshadowed by large fiscal and external imbalances.